Movement of Pots (and People) Across the Landscape: Insights from the Chemical Characterization of Mogollon Early Pithouse Pottery. Issue 1 (2nd January 2022) - Love, Lori Barkwill; Ferguson, Jeffrey R.; Creel, Darrell
Abstract : Ceramics from the Mogollon Early Pithouse period (AD 200-700) of southeastern Arizona and southwestern New Mexico consist of plain and red-slipped pottery. Even though numerous neutron activation analysis (NAA) studies have been conducted in the Mogollon region to examine pottery circulation and social networks, these studies generally focused on later types. We report the results of our NAA study that focused exclusively on Mogollon Early Pithouse pottery. We use the NAA data to explore how the pots (and people) moved across the landscape during the Early Pithouse period in the Mogollon region. We suggest that the pottery was not all locally produced. There was movement of pots, and likely people, within and between regions as well as between sites. Our analysis reveals differences in the movement of the plain brown and red-slipped ceramics. Our study shows that unpainted ceramics can provide insights into movement (pots and people) and social interaction.